The meaning of cyber pragmatic context in the Indonesian election campaign texts - Dian Marisha Putri; Mulyadi Mulyadi; Amrin Saragih; Rahmadsyah Rangkuti; Yusni Khairul Amri (Universitas Syiah Kuala, 2026)
This study aims to investigate the significance of context in the 2024 Indonesian election campaign texts. The problem focuses on the role of pragmatic cyber context, which has shifted from direct speech contexts (face-to-face) to virtual contexts (face-to-face via technology), and is oriented towards the context of the situation. This study employs a descriptive research methodology with a qualitative pragmatic approach, using data from print media and social media collected between May 2023 and February 2024. The data sources consist of five social media platforms, WhatsApp, Facebook, Twitter, TikTok, and Instagram, and five online news media outlets: Detik.com, Kompas.com, Tribunnews.com, Liputan6.com, and kumparan.com. Each source contributed 20 data points, resulting in a total of 200 data points. The data analysis process comprises the following stages: data collection, selection, coding, analysis, interpretation, and conclusion. The study’s results found that the role of pragmatic cyber context has shifted from direct to indirect (virtual or hybrid). The meaning of context in cyber text as a medium in political campaigns is found to be significant: it clarifies or elaborates on the utterance’s intent, emphasizes its substance, provides background and supports its intent, and details its intent. The role of context in campaign texts is to clarify intent, emphasize background, and support the utterance’s meaning.